The Factors Of Sanitary Hygiene Associated With The Bacteriological Quality Of Refill Water In Tanjungpinang - Weni Enjelina; M. Syahnan Purba; Zulya Erda (Faculty of Public Health, Andalas University, 2016)
The quality of drinking water in the drinking water refill depot (DAMIU) is still low. Based on the results of bacteriological testing conducted by Puskesmas in Tanjungpinang 2015, it is known that 5 samples drinking water refill (AMIU) containing coliform bacteria. This study aims to know bacteriological quality in drinking water refill and determine Factors of Hygiene sanitasion DAMIU that associated with AMIU’s bacteriological quality in Tanjungpinang city. The study design was a cross sectional study with sample of 30 DAMIU in Tanjungpinang. Sample selection is done by proportional random sampling. Data were analyzed using Chi square test. The results showed that 20% AMIU containing germs total , but for E.coli, 100% not containing. Building sanitation, processing tools sanitation and galon sanitation most of drinking water refill already eligible and not related with germs total number, only Operator hygiene that 53% eligible and related with germs total number (p value 0,017). The study conclude that 20% AMIU containing germs total. Operator hygiene factor related with germs total. To prevent the presence of germs in drinking water refill, the operator should apply hygiene behaviour and have certificate of seminar and training about hygiene and sanitary processing of DAMIU